Produksi Program Jurnal 9 Pada TV9 Perspektif Media Islam - Nur Alfiana; Lukman Hakim (Universitas Nahdlatul Ulama Surabaya, 2019)
This research aims to describe the production process of journal 9 program on TV9 in the perspective of Islamic media. The production of journal 9 programs on TV9 in the perspective of Islamic media carries the principle of